PENGEMBANGAN MEDIA INTERAKTIF DIGITAL BERBASIS ARTICULATE STORYLINE SEBAGAI UPAYA TRANSFORMASI LITERASI MEMBACA SISWA SD PASCA PISA 2022 - Putry Cahyaning Pratiwi (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The decline in Indonesia's reading literacy scores in the 2022 PISA release poses a serious challenge to national education. This crisis underscores the need for pedagogical transformation, with the focus of this research directed at restructuring conventional learning strategies to become more interactive. This study aims to develop digital gamification-based learning media using the integration of Articulate Storyline and Canva as an innovative solution to increase Elementary School students' interest and reading skills. The theoretical basis for this media development refers to Mayer's Cognitive Theory of Multimedia Learning to optimize students' visual and verbal processing. The research method used was Research and Development (R&D) with the ADDIE model. Data collection used a mixed-methods approach using validation sheets, observation sheets, questionnaires, and pre-test and post-test instruments. The results of the development are described systematically based on the ADDIE stages. The analysis phase mapped literacy degradation, while the design phase compiled game mechanics and storyboards. The development phase produced a highly valid product, with media expert validation reaching 94.5% and material expert validation at 92%. The implementation phase on 20 fifth-grade students showed a significant increase in reading comprehension skills (t-count 12.45 > t-table 2.093) with a High N-Gain score of 0.71, as well as a high practicality percentage of 89.5%. Finally, the evaluation phase confirmed that this media successfully transformed student learning behavior into active and critical learners. This innovation is strongly recommended as an adaptive pedagogical strategy for teachers to address student characteristics in the digital era.